IBM SPSS essentials : managing and analyzing social sciences data - Kulas, John T. (John Wiley & Sons, Inc., 2020)
"This book covers the nuts and bolts of SPSS usage and data entry for students learning SPSS, with a significant emphasis on managing and manipulating data. This book contains three parts. Part I provides an introduction to SPSS, discusses navigating SPSS, and contains a section on knowing your data. Next, Part II covers creating and understanding your data. In this part, readers learn how to get data into SPSS, how to manipulate the data, and also learn about descriptive statistics. Finally, Part III focuses on inferential statistics. This part includes a discussion of hypothesis testing, one-sample Z-test, T-Tests, as well as ANOVAs and correlations and regression. The authors include five appendices for further reading. These appendices discuss dealing with real-world data, troubleshooting, advanced statistics, and workbook activities. The workbook activities contain end of chapter questions and answers. Throughout the book there are now graphs such as histograms, bar plots, and scatterplots, chi-square and crosstabs, and more screen shots"--